Treatment of high-risk neuroblastoma: National protocol results of the Turkish Pediatric Oncology Group - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2017)
Background: The national protocol aimed to improve the outcome of the high risk neuroblastoma patients by high-dose chemotherapy and stem cell rescue with intensive multimodal therapy. Materials and Methods: After the 6 induction chemotherapy cycles, patients without disease progression were nonrandomly (by physicians' and/or parent's choices) allocated into two treatment arms, which were designed to continue the conventional chemotherapy (CCT), or myeloablative therapy with autologous stem cell rescue (ASCR). Results: Fifty-six percent (272 patients) of patients was evaluated as high risk. Response rate to induction chemotherapy was 71%. Overall event-free survival (EFS) and overall survival (OS) at 5 years were 28% and 36%, respectively. As treated analysis documented postinduction EFS of 41% in CCT arm (n = 138) and 29% in ASCR group (n = 47) (P = 0.042); whereas, OS was 45% and 39%, respectively (P = 0.05). Thirty-one patients (11%) died of treatment-related complications. Conclusion: Survival rates of high-risk neuroblastoma have improved in Turkey. Myeloablative chemotherapy with ASCR has not augmented the therapeutic end point in our country's circumstances. The adequate supportive care and the higher patients' compliance are attained, the better survival rates might be obtained in high-risk neuroblastoma patients received myeloablative chemotherapy and ASCR.
Keywords: Autologous stem cell rescue; high-risk neuroblastoma; treatment; Turkey; STEM-CELL RESCUE; BONE-MARROW-TRANSPLANTATION; MYELOABLATIVE THERAPY; RANDOMIZED-TRIAL; CHEMOTHERAPY; MEGATHERAPY; CLASSIFICATION; EXPERIENCE; CHILDREN; TUMORS